Identification of β Clamp-DNA Interaction Regions That Impair the Ability of E. coli to Tolerate Specific Classes of DNA Damage. - Michael T Nanfara; Vignesh M P Babu; Mohamed A Ghazy; Mark D Sutton (PLoS ONE, 2016)
The E. coli dnaN-encoded β sliding clamp protein plays a pivotal role in managing the actions on DNA of the 5 bacterial DNA polymerases, proteins involved in mismatch repair, as well as several additional proteins involved in DNA replication. Results of in vitro experiments indicate that the loading of β clamp onto DNA relies on both the DnaX clamp loader complex as well as several discrete sliding clamp-DNA interactions. However, the importance of these DNA interactions to E. coli viability, as well as the ability of the β clamp to support the actions of its numerous partner proteins, have not yet been examined. To determine the contribution of β clamp-DNA interactions to the ability of E. coli to cope with different classes of DNA damage, we used alanine scanning to mutate 22 separate residues mapping to 3 distinct β clamp surfaces known or nearby those known to contact the DNA template, including residues P20-L27 (referred to here as loop I), H148-Y154 (loop II) and 7 different residues lining the central pore of the β clamp through which the DNA template threads. Twenty of these 22 dnaN mutants supported bacterial growth. While none of these 20 conferred sensitivity to hydrogen peroxide or ultra violet light, 12 were sensitized to NFZ, 5 were sensitized to MMS, 8 displayed modestly altered frequencies of DNA damage-induced mutagenesis, and 2 may be impaired for supporting hda function. Taken together, these results demonstrate that discrete β clamp-DNA interaction regions contribute to the ability of E. coli to tolerate specific classes of DNA damage.